Empty chair technique for stress reduction in high school adolescents: a quasi-experimental investigation using the perceived stress scale - Laili Alfita; Siti Aisyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study examined the efficacy of the empty chair technique in reducing stress levels among stressed female adolescents in secondary education settings. A quasi-experimental, one-group pretest-posttest design was employed. The sample comprised 74 high school female students selected through purposive sampling based on pre-established stress symptomatology criteria. Psychological distress was assessed using the Perceived Stress Scale (PSS-10), a 10-item unidimensional instrument with demonstrated validity (Cronbach's α = 0.81) and internal consistency across adolescent populations. The empty chair technique intervention was administered across 8 weekly sessions (60-minute duration per session), conducted by trained Gestalt counselors following manualized protocol. Data were analyzed using paired-samples t-tests with calculation of Cohen's d effect sizes and 95% confidence intervals. Mean perceived stress scores decreased significantly from pretest (M = 18.59, SD = 9.18) to posttest (M = 15.85, SD = 9.57), representing a reduction of 2.74 points (95% CI: 1.32–4.16). Paired-samples t-test revealed this reduction was statistically significant, t(73) = 2.91, p = 0.004, with a moderate effect size (Cohen's d = 0.29). The magnitude of change suggests clinically meaningful stress reduction, as approximately 68% of participants demonstrated measurable improvement exceeding one standard error of measurement. The Empty Chair Technique demonstrates efficacy as a school-based, brief psychosocial intervention for reducing psychological stress among adolescents. Future investigations should employ randomized controlled designs with longer follow-up assessments, standardized adherence measures, and multi-method outcome evaluation to establish robust evidence for dissemination within school counseling programs.